Magnetic resonance evaluation of rotator cuff healing after surgical repair of large and massive lesions using the load-sharing rip-stop construct: encouraging results - Raul Meyer Kautsky, MD; Benno Ejnisman, MD, PhD; Juarez Leite Junior, MD; Eduardo Antônio de Figueiredo, MD, PhD; Ricardo Azeredo Costa, MD; Jair Simmer Filho, MSc, MD (JSES International)
Background: The purpose of this study is to evaluate the tendon healing rate in large and massive tears using magnetic resonance imaging (MRI) based on the Sugaya classification and to present the functional outcomes (American Shoulder and Elbow Surgeons, University of California, Los Angeles, and visual analog scale scores) in patients who underwent the Load-Sharing Rip-Stop (LSRS) suture technique. These patients often present with retracted lesions, limited mobility, poor-quality tissues prone to tearing, medial tears, and/or insufficient bone quality (osteopenia or osteoporosis). Methods: Retrospective evaluation of patients aged > 55 years who underwent arthroscopic rotator cuff repair due to retracted tears (that after appropriate releases, it was not possible to cover more than 50% of the tendon footprint on the greater tuberosity upon rotator cuff traction), operated between 2014 and 2022, using the LSRS technique, and who underwent a minimum follow-up of 1 year, including postoperative MRI assessment. Results: Eighteen shoulders were included in the study and all of them performed a postoperative MRI; 1 patient experienced tendon rerupture on follow-up MRI, corresponding to a 5.56% failure rate. In the functional analysis, 16 shoulders (88.89%) scored above 80 on the American Shoulder and Elbow Surgeons score and had satisfactory results on the University of California, Los Angeles score (rated as excellent and good). Conclusion: In an average follow-up of 28 months, the LSRS suture technique demonstrated satisfactory functional outcomes and a good healing rate in patients with retracted and low-mobility rotator cuff injuries. These findings reinforce the idea that the LSRS technique can be a valuable option in managing these challenging cases.